Development and validation of a risk assessment tool for uncontrolled type 2 diabetes among patients in South Karnataka, India - Deepak Anil; Sunil Kumar Doddaiah; Rajendra Prasad Shivaswamy; Arun Gopi; Sayana Basheer; Mysore Ramakrishnaiah Narayana Murthy (BMJ Public Health)
Introduction Diabetes is a chronic medical condition with severe complications mainly caused due to unhealthy lifestyles in genetically susceptible individuals. This study attempts to develop a non-invasive risk assessment tool to identify patients with uncontrolled type 2 diabetes mellitus (T2DM) in southern India.Methodology An exploratory study was conducted among 545 patients with T2DM in the Mysuru district, South India for 6 months. A prevalidated questionnaire was used to collect data. Univariate and multivariate logistic regression analysis was performed to develop the risk score. Receiver-operating characteristic (ROC) curve and area under the curve (AUC) were used to evaluate the cut-off for the risk score. The risk score is specifically designed for the population of South Karnataka, India.Results Out of the 545 study participants, the prevalence of uncontrolled diabetes was 59.9%. Physical activity, duration of diabetes, diabetic diet, regular health check-ups, history of hypertension, smoking history and alcohol consumption were factors significantly associated with uncontrolled diabetes (p<0.05). For an optimum cut-off point of >13.50, the risk assessment model showed a moderate sensitivity of 71.3%, specificity of 61%, positive predictive value of 73.2% and negative predictive value of 58.3%. The ROC curve was plotted for the model with an AUC of 0.726 (95% CI 0.683 to 0.769).Conclusion This study developed ‘Diabetes Care’, a simple web-based, non-invasive and inexpensive tool for identifying individuals at risk of developing uncontrolled T2DM in the future.